Based on Genetic Algorithm to Analyze the Anti-Penetration Properties and Optimize the Structure of Ti-Al3Ti-Al Laminated Composites - Li, Yaoming; Zhang, Huang; Yuan, Meini (Frontiers in Materials, 2022)
A coupled finite element genetic algorithm technique was used to optimize the arrangement order and layer thickness ratios of Ti-Al3Ti-Al laminated composites. Moreover, the damage evolution, the energy conversion and the stress distribution of TC4-Al3Ti-Al laminated composites under impact were analyzied. The results showed that: TC4-Al3Ti-Al Laminated Composites with layer thickness ratio 3:14:4 has the optimum anti-penetration properties; The projectile kinetic energy is mainly converted into the internal energy of bullet target system; During the penetration process of TC4-Al3Ti-Al targets, the TC4 layer is shear failure, the Al layer is a petal-like failure, the failure mode of Al3Ti layer is fragmentation; With the number of layers increases, the anti-penetration properties of TC4-Al3Ti-Al targets are gradually increasing. However, when the numbers of layer are more than 30 layers, the numbers of layers has little effect on the anti-penetration performance of this composites.